Surface modification of metallic orthopedic implants for anti-pathogenic characteristics - Pal Singh Sidhu, Varinder; Marchi, Juliana; Borges, Roger; Ahmadi, Elahe (Journal of Composites and Compounds, 2022)
Bacterial infection is one of the main reasons for the long-term failure of orthopedic implants. Despite remarkable progression in antimicrobial drugs, implant-associated infection (IAI) remains difficult to treat, which is resulted from bacterial resistance against antibiotics. As a result, there is an urgent need to develop alternative approaches. The present review highlights surface modification of the orthopedic implants as a promising approach to inhibit bacterial infection. This approach can be classified into two groups: (1) bacteriostatic (anti-adhesive), and (2) bactericidal (contact-killing/release-killing) surfaces. Their combination, which is considered as bacteriostatic-bactericidal bi-functional surface, can provide a more robust approach against dangerous pathogenic species. New approaches and future perspectives in this inspiring field are also provided.